SUSTAINABLE HR RESEARCH EVOLUTION IN 20 YEARS FROM 2005 UNTIL 2025 - Ade Suhara; Amallia; Decut Della; Suyana Hadi; Nanny Mayasari (LPSDI Bina Patria, 2025)
This study conducts a comprehensive bibliometric analysis to examine the evolution of sustainable human resource management (HRM) research over a 20-year period from 2005 to 2025. Utilizing data extracted from the Scopus database and analyzed through VOSviewer, the research maps the intellectual structure, thematic concentrations, and global collaboration networks within the field. The findings reveal a steadily growing body of literature, with core themes centered on corporate social responsibility, green HRM, strategic alignment, and employee well-being. Co-authorship and country collaboration analyses indicate a dense network of influential scholars and cross-regional partnerships, led by the United Kingdom, United States, India, and China. Keyword co-occurrence and temporal mapping highlight an evolving research agenda, with emerging topics such as artificial intelligence, sustainable development goals, and mental health gaining traction in recent years. This study contributes to the field by offering a synthesized overview of key research trends, identifying conceptual gaps, and suggesting future directions for scholarly inquiry into sustainable HRM within the broader sustainability discourse.